Efektivitas Konseling Kelompok dalam Meningkatkan Keterampilan Sosial Siswa di Sekolah - Aisyah Ariesca Putri; Nabilla Khairunnisa. S; Hana Pratiwi; Ririn Ayu Anjar Wani; Ratna Sari Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to evaluate the effectiveness of group counseling in improving students' social skills in schools through an analysis of 20 articles that meet the inclusion criteria. The results of the review show that group counseling is effective in developing various aspects of students' social skills, including interpersonal communication, cooperation, empathy, and confidence. Various approaches are applied in the implementation of group counseling, such as modeling techniques, role playing, assertive approaches, cognitive behavioral therapy (CBT), and group discussions. The program also creates a safe space for students to share experiences, gain emotional support, and learn to manage emotions and build positive social relationships. Factors that support the success of the program include counselor skills, a good program structure, and support from teachers, parents, and the school environment. Based on these findings, group counseling can be considered as one of the effective strategies to support students' social and emotional development and improve the quality of learning in schools.